Telemedicine Effectiveness in Reducing Out-of-Pocket Expenditure and Hospital Queues: Evidence from Indonesia - Derry Trisna Wahyuni S; Nurul Adzkia Ghearizky (Journal of Health Service Administration and Hospital Management, 2026)
The rapid escalation of healthcare demand in Indonesia has exacerbated systemic inefficiencies, characterized by high out-of-pocket (OOP) expenditures and hospital congestion. This study evaluates the effectiveness of telemedicine in mitigating these burdens within the Indonesian healthcare ecosystem. Utilizing a quantitative cross-sectional secondary analysis, the research synthesized datasets from 2023-2024, including the National Socio-Economic Survey (Susenas, n=345,000 households), Satu Data JKN portal (n=248 million participants), and SIRANAP metrics. A Cost-Effectiveness Analysis (CEA) framework was employed to calculate direct non-medical cost savings and labor productivity gains based on Sakernas hourly wage data. Results demonstrate that telemedicine integration facilitated a 66.7% reduction in total OOP expenditure per encounter, with a significant difference observed between digital and physical consultations (p < .001). Furthermore, a 20.7% national decrease in physical hospital queuing was recorded, resulting in a mean time-saving of 4.1 hours per patient (t(150) = 4.32; p < .001). These findings indicate that digital health adoption enhances allocative efficiency within referral facilities. Implications suggest that while digital platforms improve service throughput, efficacy correlates with regional internet penetration. It is concluded that telemedicine reduces financial friction and hospital load, though its impact is non-uniform across the archipelago. Future policy should focus on infrastructural equity in remote regions to ensure the sustainability of digital health access.